Beberapa Penelitian Terhadap Konsep Azab Kubur Menurut Tuan Minal Melalui Karyanya Kashf al-Ghaybiyyah: A Study of Some Aspects on the Torment in the Grave according to Tuan Minal in His Work Kashf al-Ghaybiyyah - Utut , Mohd Nasir; Abd Latif, Faizuri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The torment in the grave is one of the questions of faith comprised in the debate on al-ghaybiyyat and al-sami‘yyat (the knowledge of the unseen) which is something that is not known except through the Qur’anic verses and Hadith. Although there are many proofs from the Qur’an and Hadith validate the truth of the torment in the grave, there are those who still dispute its existence. Among them are the Mu‘tazilites who claim that they witnessed the situation of a corpse that has died without any effect of being tortured. In addition, the atheists and zindiqs also denied the matter with the argument that they had dug a grave but did not find any evidence of archangel beating or torturing corpses. Therefore, a qualitative study using documentation method is carried out to unravel all the bewilderment through the authoritative works of Malay scholars. For this purpose, the book of Kashf al-Ghaybiyyah which is a Malay scholarly work will be the focus of research. This work is chosen because it discusses many issues of al-sam‘iyyat including the torment in the grave and its arguments. This study found that the strength within Kashf al-Ghaybiyyah’s arguments, which expounded many texts of the Qur’an and Hadith are capable to prove the validity of the torment in the grave.